The effect of flaxseed supplementation on sex hormone profile in adults: a systematic review and meta-analysis - Musazadeh, Vali; Nazari, Ahmad; Natami, Mohammad; Hajhashemy, Zahra; Kazemi, Kimia Sadat; Torabi, Fereshte; Moridpour, Amir Hossein; Vajdi, Mahdi; Askari, Gholamreza (Frontiers in Nutrition, 2023)
Inconsistent data suggest that flaxseed supplementation may have a role in sex hormones. We aimed to carry out a systematic review and meta-analysis of randomized controlled trials (RCTs) investigating effects of flaxseed supplementation on sex hormone profile. PubMed, Scopus, Embase, Cochrane Library, Web of Science databases, and Google Scholar were searched up to March 2023. Standardized mean difference (SMD) was pooled using a random-effects model. Sensitivity analysis, heterogeneity, and publication bias were reported using standard methods. The quality of each study was evaluated with the revised Cochrane risk-of-bias tool for randomized trials, known as RoB 2. Finding from ten RCTs revealed that flaxseed supplementation had no significant alteration in follicle-stimulating hormone (FSH) (SMD: −0.11; 95% CI: −0.87, 0.66: p = 0.783), sex hormone-binding globulin (SHBG) (SMD: 0.35; 95% CI: −0.02, 0.72; p = 0.063), total testosterone (TT) levels (SMD: 0.17; 95% CI: −0.07, 0.41; p = 0.165), free androgen index (FAI) (SMD = 0.11, 95% CI: −0.61, 0.83; p = 0.759), and dehydroepiandrosterone sulfate (DHEAS) (SMD: 0.08, 95%CI: −0.55, 0.72, p = 0.794). Flaxseed supplementation had no significant effect on sex hormones in adults. Nevertheless, due to the limited included trials, this topic is still open and needs further studies in future RCTs.